(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The historical stages of the EU budgetary management system are framed. In particular such periods are marked out: formation of the primary system (1951–1975); budgetary crisis (1976–1987); reform of the budgetary system (Delors I package) (1988–1992); confirmation of budgetary reforms (Delors II package) (1993–1999); preparation of the system to the greatest enlargement (package «Agenda–2000») (2000–2006); policy challenges and budgetary means of the enlarged EU (since 2007). Also the primary innovations that have taken place in each of the periods and the factors that caused them were identified. The patterns thus detected led to the author’s suggestion as for the development trends of the budgetary system of the EU in the near future. Namely, it is concluded that, in the event of further enlargement of the EU to the «poor» and «agrarian» East, there will be a need for significant structural changes to the EU budget reasoned by the increased tension among net-contributors and net-recipients of the common budget.